Mycorrhizal tomato plants fine tunes the growth‐defence balance upon N depleted root environments. (27th December 2017) - Sánchez‐Bel, P.; Sanmartín, N.; Pastor, V.; Mateu, D.; Cerezo, M.; Vidal‐Albalat, A.; Pastor‐Fernández, J.; Pozo, M.J.; Flors, V.
Abstract: In low nutritive environments, the uptake of N by arbuscular mycorrhizal (AM) fungi may confer competitive advantages for the host. The present study aims to understand how mycorrhizal tomato plants perceive and then prepare for an N depletion in the root environment. Plants colonized by Rhizophagus irregularis displayed improved responses to a lack of N than nonmycorrhizal (NM) plants. These responses were accomplished by a complex metabolic and transcriptional rearrangement that mostly affected the gibberellic acid and jasmonic acid pathways involving DELLA and JAZ1 genes, which were responsive to changes in the C/N imbalance of the plant. N starved mycorrhizal plants showed lower C/N equilibrium in the shoots than starved NM plants and concomitantly a downregulation of the JAZ1 repressor and the increased expression of the DELLA gene, which translated into a more active oxylipin pathway in mycorrhizal plants. In addition, the results support a priorization in AM plants of stress responses over growth. Therefore, these plants were better prepared for an expected stress. Furthermore, most metabolites that were severely reduced in NM plants following the N depletion remained unaltered in starved AM plants compared with those normally fertilized, suggesting that the symbiosis buffered the stress, improving plant development in a stressed environment. Abstract : Tomato plants colonized by Rhizophagus irregularis displayed improved responses to a lack of N compared with nonmycorrhizal plants. AM plants displayed a metabolic and transcriptional rearrangement prioritizing the stress responses over growth under N depletion conditions. AM plants also showed a more active oxylipin pathway compared with NM plants under N depletion conditions. Mycorrhizal plants are more prepared to cope with environmental stress than NM plants.